An Internationalization Model to Enter the Northern Triangle Market (2013)
An internationalization model is proposed for a Colombian company specialized in design and consulting engineering services related to the energy sector. The study of these services is relatively new in internationalization and competitiveness, therefore of great interest for research purposes. The model is created with the purpose of conquering the Northern Triangle market (Guatemala, Honduras, El Salvador). Different internationalization theories,such as the Eclectic Paradigm, the Uppsala Model and the Five Competitive Forces were considered. Different assessments were carried out based on qualitative and quantitative data through the case study method in which analyses were performed to generate and evaluate the main variables in the model. Outcomes assure that, HMV Ingenieros Ltda (a Colombian company) is prepared to start commercial presence in the Northern Triangle considering the Step-by-Step model as the way to reach the studied market. In addition, analysis of macroeconomic trends finds Guatemala as the best potential market.